Impact of Zeolite Structure on Entropic–Enthalpic Contributions to Alkane Monomolecular Cracking: An IR Operando Study. Issue 21 (24th March 2018) - Kadam, Shashikant A.; Li, Haoguang; Wormsbecher, Richard F.; Travert, Arnaud
Abstract: The monomolecular cracking rates of propane and n ‐butane over MFI, CHA, FER and TON zeolites were determined simultaneously with the coverage of active sites at reaction condition using IR operando spectroscopy. This allowed direct determination of adsorption thermodynamics and intrinsic rate parameters. The results show that the zeolite confinement mediates enthalpy–entropy trade‐offs only at the adsorbed state, leaving the true activation energy insensitive to the zeolite or alkane structure while the activation entropy was found to increase with the confinement. Hence, relative cracking rates of alkanes within zeolite pores are mostly governed by activation entropy. Abstract : In the search of the reactant state : The determination of the concentration of acid site‐alkane complexes within zeolite pores at reaction conditions allows for a consistent determination of adsorption and intrinsic rate terms governing the monomolecular cracking activity.